Boosting High-Rate Zinc-Storage Performance by the Rational Design of Mn2O3 Nanoporous Architecture Cathode - Feng, Danyang; Gao, Tu‑Nan; Zhang, Ling; Guo, Bingkun; Song, Shuyan; Qiao, Zhen‑An; Dai, Sheng (Nano-Micro Letters, 2019)
Manganese oxides are regarded as one of the most promising cathode materials in rechargeable aqueous Zn-ion batteries (ZIBs) because of the low price and high security. However, the practical application of Mn2O3 in ZIBs is still plagued by the low specific capacity and poor rate capability. Herein, highly crystalline Mn2O3 materials with interconnected mesostructures and controllable pore sizes are obtained via a ligand-assisted self-assembly process and used as high-performance electrode materials for reversible aqueous ZIBs. The coordination degree between Mn2+ and citric acid ligand plays a crucial role in the formation of the mesostructure, and the pore sizes can be easily tuned from 3.2 to 7.3 nm. Ascribed to the unique feature of nanoporous architectures, excellent zinc-storage performance can be achieved in ZIBs during charge/discharge processes. The Mn2O3 electrode exhibits high reversible capacity (233 mAh g−1 at 0.3 A g−1), superior rate capability (162 mAh g−1 retains at 3.08 A g−1) and remarkable cycling durability over 3000 cycles at a high current rate of 3.08 A g−1. Moreover, the corresponding electrode reaction mechanism is studied in depth according to a series of analytical methods. These results suggest that rational design of the nanoporous architecture for electrode materials can effectively improve the battery performance. Highlights: 1 Highly crystalline Mn2O3 materials with tunable pore sizes are obtained and employed as high-performance cathode materials for reversible aqueous Zn-ion battery. 2 The Zn/Mn2O3 battery exhibits significantly improved rate capability and remarkable cycling durability due to the introduction of nanoporous architecture. 3 The Zn2+/H+ intercalations mechanism is put forward for the Zn/Mn2O3 battery.